The future of Islam - Esposito, John L. (Oxford University Press, 2010)
John L. Esposito is one of America's leading authorities on Islam. In this brilliant portrait of Islam today- and tomorrow- he draws on a lifetime of thought and research to provide an accurate, richly nuanced, and revelatory account of the fastest growing religion in the world.